Do Corridors Promote Connectivity for Bird-Dispersed Trees? the Case of Persea Lingue in Chilean Fragmented Landscapes - Vergara-Egert, P; Perez-Hernandez, C (Kluwer Academic Publishers, 2015)
Disentangling the contribution of corridors to landscape connectivity is crucial for adopting efficient measures in conservation, but their actual role in heterogeneous landscapes is not yet fully understood. We assessed the hypothesis that corridors, consisting of hedgerows and riparian vegetation strips, are important landscape elements promoting functional connectivity for the lingue (Persea lingue), a tree endemic to southern Chile and Argentina whose seeds are mainly dispersed by the habitat generalist austral thrush (Turdus falcklandii). For this purpose, we used empirical estimates of seed production, fruit consumption and bird movement patterns, in combination with a seed dispersal model and a graph-theoretical approach for network connectivity analysis. We found that for this plant-animal interaction, the hypothesis mentioned above is not supported. Functional connectivity decreased as the structural connectivity provided by corridors increased, and stepping stones were much more effective connectivity providers than corridors. Our findings are not generalizable to other situations because thrushes contribute to the dispersal of seeds along narrow and sinuous corridors, which provide unsuitable conditions for the establishment of lingues. We conclude that (a) the effectiveness of corridors for promoting connectivity and successful dispersal is landscape- and species-specific; and that (b) effective conservation of Chilean forest biodiversity involves a tradeoff between enhancing the availability of stepping stones and providing corridors of sufficient width and appropriate shape to meet the needs and dispersal modalities of different species. © 2014 Springer Science+Business Media Dordrecht